Synthesis and Biological Evaluation of New cis-Restricted Triazole Analogues of Combretastatin A-4 - Lidia Prieto; Daniel Gaviña; Marcos Escolano; María Cánovas-Belchí; María Sánchez-Roselló; Carlos del Pozo; Eva Falomir; Santiago Díaz-Oltra (Molecules)
The natural products combretastatins A-1 and A-4 are potent antimitotic and vascular-disrupting agents through their binding at the colchicine site in tubulin. However, these compounds suffer from a low water solubility and a tendency to isomerize to the inactive trans stilbenes. In this study, we have prepared a series of 18 cis-restricted triazole analogues of combretastatin A-4 (CA-4), maintaining, in all cases, the 3,4,5-trimethoxy phenyl ring A, with the aim of investigating the substitution pattern on the B-ring in a systematic way. To this end, cytotoxic activities of the cis-restricted analogues of CA-4 prepared were determined in two tumor cell lines, namely, HT-29 and A-549, as well as in the non-tumor cell line HEK-293, to pre-evaluate the selectivity profile of the compounds for the tumor cell lines. The main conclusion was the essential presence of methoxyl or ethoxyl groups at the para position of the B-ring in order to obtain good antitumor activities. Thus, the more active compounds in our study displayed IC50 values in the nanomolar range for the tumor cell lines but not for the normal cells. Consequently, these triazole analogues of CA-4 could serve as promising alternatives to the natural product, although further studies about their biological activity are essential in order to fully determine their viability as therapeutic agents in the treatment of cancer.